MANAJEMEN PEMBELAJARAN BERBASIS AKREDITASI DI PONDOK PESANTREN - M Iswantir; Zulfani Sesmiarni; Sulha Dewi Hana (HIKMAH: JURNAL PENDIDIKAN AGAMA ISLAM, 2022)
Community Service Based on the Study Program of the Research and Community ServiceInstitute (LP2M) IAIN Bukittinggi is the result of a study program-based service that theauthor carried out with the title Accreditation-Based Learning Management Assistance at theMuallimin Islamic Boarding School, Sawah Dangka, Agam Regency, West Sumatra. Thisservice is motivated by the low understanding of leaders and teachers in managing learningthat refers to the accreditation standards of Islamic boarding schools. The purpose of thisservice is to provide assistance and empowerment of leaders and teachers in managingaccreditation-based learning management, as well as see a comparison of the knowledge ofleaders and teachers about accreditation-based learning management before and afterempowerment. The object of this empowerment is the leader and the teacher assembly. Theempowerment method used is Participatory Action Research (PAR). The results ofempowerment and service can be concluded that first, teacher document readiness inaccreditation-based learning management, it was concluded that 55% of teachers stated thatthey had document readiness, 24% of teachers stated that they did not have documents, and21% of teachers expressed doubts between having documents with do not have documents.Second, the results of monitoring and evaluation of the increase in teacher knowledge afterparticipating in the activity concluded that 79.5% stated that teacher knowledge hadincreased. And third, the level of teacher satisfaction in empowerment and mentoring ofaccreditation-based learning management at the Muallimin Sawah Dangka Islamic BoardingSchool, Agam Regency, West Sumatra, it was found that most of the teachers gave anassessment of being satisfied with the implementation of activities, namely 73.8%, a smallpart stated very satisfied, namely 19 %, and a small part also stated that 7.1% said they werequite satisfied.